The role of IL-4 and IL-13 in pulmonary tuberculosis using gene-deficient mice and protective efficacy of the purine-deficient auxotroph of Mycobacterium tuberculosis - Brown, Najmeeyah (Division of Immunology, 2014)
Bibliography: leaves 75-90.